Oxford urdu k guldasta Nargis grade 4 - Farooqui, Fozia Ahsan (Karachi : Oxford university press, 2023)
"Oxford Urdu Ka Guldasta Nargis (Grade 4)" is a collection of Urdu stories, poems, and rhymes for fourth-grade students. The book helps young readers improve their Urdu language skills, focusing on vocabulary, comprehension, and sentence formation. Through a variety of interesting and age-appropriate content, it introduces students to more complex themes and moral lessons. The book is designed to engage children with colorful illustrations and captivating narratives, making learning Urdu both enjoyable and educational.
Keywords: Urdu : Textbook